ANALISIS IMPLEMENTASI PEMBELAJARAN TEMATIK DI KELAS RENDAH SDN 06 EMANG BEMBAN - Yanlatiabina, Franciska; Ason, Ason; Apsari, Nurul (JURNAL PENDIDIKAN DAN PEMBELAJARAN SEKOLAH DASAR, 2023)
This study aims to (1) describe the implementation of thematic learning by low grade teachers (2) describe the constraints faced by low grade teachers when implementing thematic learning (3) describe the solutions designed and carried out by low grade teachers in overcoming obstacles thematic learning.This research was conducted in the lower grades of SDN 06 Emang Bemban, Pinoh Selatan District, Melawi Regency. This study uses a type of qualitative research through observation, interviews and documentation. The subjects in this study were low grade teachers at SDN 06 Emang Bemban and the object of this study was the implementation of thematic learning in low grades. Data collection techniques using observation, interviews and documentation. The research instrument used was observation sheets and interviews.The results of this study indicate that low grade teachers have implemented thematic learning, but there are several obstacles in the implementation process, namely; First, the lack of students' understanding of learning makes low grade teachers take initiatives to help students, one of the initiatives taken is to make learning separate or per subject. Second, the lack of use of learning media. Third, there are still teachers who have not been able to develop thematic lesson plans. By finding some of these obstacles, low grade teachers collaborated with the Education Unit at SDN 06 Emang Bemban to realize thematic learning that was carried out without experiencing any problems.Â